Adoption of information technology tools in micro, small and medium enterprises of India. (1st January 2013) - Singh, Brijesh; Narain, Rakesh; Yadav, R.C.
Effective utilisation of information technology (IT) is essential to compete in the global environment. As the contribution of micro, small and medium enterprises (MSMEs) in generating employment, manufacturing output and export is significant, in most of the countries, there is a need to make them more informative, competitive and agile. The use of advanced manufacturing technologies (AMT), together with IT, provides a means for improving performance, gaining global recognition and bringing growth. This paper is based on the survey of 84 MSMEs of India carried out to investigate the state of IT adoption for various functions and areas, and the hurdles encountered in the way of growth and competitiveness.